PENYULUHAN KESEHATAN TENTANG TB PARU DI LK 1 RT 06 DESA SUMBER AGUNG KECAMATAN KEMILING BANDAR LAMPUNG - Pribadi, Teguh; Wahyudi, Wahid Tri (JURNAL KREATIVITAS PENGABDIAN KEPADA MASYARAKAT (PKM), 2018)
ABSTRACTEfforts that can be made to prevent transmission and treatment of pulmonary TB include, among others, treating positive smear positive pulmonary TB patients as a source of transmission until healed, recommending that patients cover their nose and mouth when coughing and sneezing, if coughing up phlegm is collected in container with contains of 5% lisol or dry soil, improves housing and environmental conditions, patients recommended staying in isolation room, especially during the first 2 months of treatment. The goal after the extension activity is expected to increase public knowledge and be able to maintain and understand the dangers of pulmonary TB, especially the Sumber Agung community. The activities carried out in the form of counseling using leaflets, LCD projectors and demonstrations. There is a change in knowledge of the community in the village a great source of pulmonary TB disease and ways of prevention and treatment. Thus, providing education through counseling the community about the prevention and treatment of pulmonary TB. Keywords: Prevention, Treatment, Tuberculosis